Educational Cinema Techniques Guide for Accelerating Optimism Among Senior High School Students - Flurentin, Elia; Setiyowati, Arbin Janu; Mahardika, Jasmine Anantiya (citeus, 2025)
This study seeks to develop a group counseling guide media using educational cinema techniques to enhance students' optimism in State Senior High School 1 Singosari, Malang. This study adopted the Research and Development research model developed by Borg and Gall, comprising seven research stages, including: (1) data collection stage, (2) research planning stage, (3) initial product development, (4) trial phase, (5) product revision stage, (6) initial field trial phase, (7) final product stage. In this study, an instrument was employed to assess the acceptability of the prototype which had been developed. The data applied in this study was quantitative and qualitative data. The quantitative data was obtained using percentage descriptive techniques. Qualitative data was also obtained from criticism, suggestions, and input from experts and potential product users. The results of the service media expert test, service material expert test, and prospective users showed a high score. The obtained score indicates that the prototype meets the accessibility criteria of accuracy, usability, convenience, and attractiveness, as well as the criteria of being very accurate, very useful, very easy to use, and very interesting to use.